ChemInform Abstract: Air‐Stable Triazine‐Based Ni(II) PNP Pincer Complexes as Catalysts for the Suzuki—Miyaura Cross‐Coupling. Issue 47 (3rd November 2016) - Mastalir, Matthias; Stoeger, Berthold; Pittenauer, Ernst; Allmaier, Guenter; Kirchner, Karl
Abstract: One of the title complexes is successfully applied in the title coupling reaction of aryl boronic acids, pinacol esters and potassium phenyltrifluoroborate with aryl iodides, bromides, chlorides, tosylates, triflates, carbamates and pivaloates.